SUPERVISI AKADEMIK KEPALA SEKOLAH TERHADAP KINERJA GURU PAK DALAM MENINGKATKAN HASIL BELAJAR - Maria Andriani; Hermania Bhoki; Yosep Belen Keban (JAPB: Jurnal Agama, Pendidikan dan Budaya, 2023)
This research aims to analyze the role of the principal's academic supervision on the performance of Catholic religious education teachers in improving Catholic religious education learning outcomes at SDK Harubala. The research was conducted at SDK Harubala, Ile Boleng District, East Flores Regency. The research data source consisted of four people, including 2 teachers, 1 school principal, and 1 regional coordinator. The research method used is a qualitative descriptive method with data collection techniques through interviews, observation and documentation. The collected data was analyzed using data reduction techniques, data presentation and drawing conclusions. The results of the research show that the academic supervision carried out by the principal at SDK Harubala has been carried out well, although its consistency still needs to be improved. The performance of Catholic religious education teachers is considered good in learning preparation, but they need to improve learning methods in the classroom so that students feel comfortable and focus on the learning process. Students have not achieved good learning outcomes in the aspects of spiritual attitudes, social attitudes, knowledge of Catholic religious education, and religious life skills, so there is a need for ongoing guidance from Catholic religious education teachers